A Dyadic View on the Post-separation Network of Single Mothers - Mortelmans, Dimitri; Verheyen, Wendy (Qualitative Sociology Review, 2021)
Many empirical studies have focused on the quantitative changes in the social networks of divorced and separated people. In this qualitative study, we use interviews with dyads to construct a two-sided view of the support network after separation. The aim of the study is to gain insight into the needs for support after a relational breakup. Including a network member in the analysis enables a more detailed view on the interaction at hand in the bond between these women and their supportive network members. The results show that personal coping resources are left untouched. Giving advice on ones daily activities is counter-productive. This is better understood by non family members compared to the women’s parents (especially the mother). With respect to the reciprocity in these relationships, network members do not expect a return in the period after the separation.